New macroeconomics - Mulay, Apek (Economics collection., 2018)
According to the National Bureau of Economic Research (NBER), a deep recession started in the United States in December 2007 and ended in June 2009. However, most people recognize that even though the recession was said to be over, its aftereffects lingered well into the next decade, and even in 2017, some ten years later, governments in America and around the world were struggling with problems of low growth, wage stagnation, and high poverty. Most economists were caught off guard, and they began to look for new ideas that may be appropriately called NEW MACROECONOMICS. In the spirit of scientific inquiry, it is important to compare accepted theory with reality. Keynesianism remains the dominant paradigm in macroeconomics, and the 2008 meltdown revived Keynesian prescriptions. But the subsequent anemic and fraught recovery also intensified criticism of Keynesianism. This book examines consensus economics in the context of recent developments. I confess that this book could be interpreted as a highly personal perspective. It draws upon ideas from a few well-known experts such as Professors Joseph Stiglitz, Paul Krugman, and Ravi Batra through the lens of my own experience in the technology sector. The book shows that a new theory, known as the wage-productivity model, explains almost every macroeconomic experience of the global economy since 1980. This is an incredible claim, but those who have examined it agree with my assessment. The forecasting record of this theory is also stunning. It predicted the Great Recession a year before it started, arguing that a steep downturn would start in 2007 and then linger in one form or another until 2019. You have to read this theory to believe it.